Pericardial effusion: case report - Dávila F., Roberto (2015)
Pericardial effusion is described as an abnormal accumulation of fluid in the pericardial cavity, which can lead to a cardiac tamponade associated with neoplasms. It is described the clinical case of a Golden Retriever dog, 10 years old, taken to consultation due to anorexia, abdominal distension and depression. At clinical examination, faintly audible heart sounds, weak femoral pulse and tachypnea were detected. Laboratory tests showed anemia and kidney failure. The ultrasound determined hydropericardium and a tumor mass on the basis of the right heart. The radiological study showed increased heart silhouette. It was concluded that the injury was consistent with cardiac tamponade by pericardial effusion due to a cardiac mass.